The Graduation Seminar: A Space for the Consolidation of Professional Competencies in the Bachelor's Degree (Docentes 2.0 Journal, 2025)
The curricular space strengthens the articulation between theory and professional practice, consolidating key competencies for contextualized and relevant educational intervention. This research aimed to describe experiences in the graduation seminars for the bachelor’s degree in educational Intervention (LIE) at the National Pedagogical University 144, Ciudad Guzmán, to demonstrate their viability in consolidating the components of the graduate profile. This research was conducted within the interpretive paradigm, using the case study method, with a qualitative approach and descriptive design. A research population of 35 students was selected, enrolled in an eighth-semester group. The research techniques implemented included text analysis (UPN normative documents) and direct observations of the products generated in the courses. Analysis of the final versions of the graduation document shows that students completed with at least 80% progress, which allowed them not only to pass the course but also to achieve a favorable prognosis toward obtaining an academic degree. The research findings confirm positive experiences regarding the use of technology and digital media to ensure communication between advisors and students. This provided certainty regarding the completion of the graduation process. Thus, the evaluation was useful in redesigning the graduation seminar. It has become a space for construction, reflection, and feedback based on the contributions of advisors and students.
Keywords: Qualification; educational intervention; professional skills; initial training; reception document